2014
DOI: 10.1155/2014/689456
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Education on Chinese Version of Montreal Cognitive Assessment in Detecting Amnesic Mild Cognitive Impairment among Older People in a Beijing Rural Community

Abstract: To assess the influence of education on the performance of Chinese version of Montreal cognitive assessment (C-MoCA) in relation to the mini-mental state examination (MMSE) in detecting amnesic mild cognitive impairment (aMCI) among rural-dwelling older people C-MoCA and MMSE was administered and diagnostic interviews were conducted among community-dwelling elderly in two villages in Beijing. The performance of C-MoCA and MMSE in detecting aMCI was evaluated by the area under the ROC curve (AUC). Effect size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 17 publications
6
34
0
2
Order By: Relevance
“…Our findings are in accord with several emerging studies in Chinese populations that indicate relatively lower levels of accuracy, Sn, and Sp than those previously reported [19,20,22]. Yu et al [19], conducting a study in Beijing involving a large heterogeneous population-based sample, reported a modest accuracy (AUC = 0.71) with Sn = 0.69 and Sp = 0.64 at a reduced cut-off of 22.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in accord with several emerging studies in Chinese populations that indicate relatively lower levels of accuracy, Sn, and Sp than those previously reported [19,20,22]. Yu et al [19], conducting a study in Beijing involving a large heterogeneous population-based sample, reported a modest accuracy (AUC = 0.71) with Sn = 0.69 and Sp = 0.64 at a reduced cut-off of 22.…”
Section: Discussionsupporting
confidence: 92%
“…Yu et al [19], conducting a study in Beijing involving a large heterogeneous population-based sample, reported a modest accuracy (AUC = 0.71) with Sn = 0.69 and Sp = 0.64 at a reduced cut-off of 22. Zhou et al [22] evaluated the MoCA among rural-living elderly subjects in two villages in the outskirts of Beijing and reported an AUC of 0.72 (at a cut-off of 20/21) with Sn = 0.75 and Sp = 0.62. Both studies showed that the MoCA performed no better than the MMSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, certain items on the MoCA are likely to be influenced by education [43], for instance, clock drawing, phonemic verbal fluency, and verbal abstraction [59].…”
Section: Discussionmentioning
confidence: 99%
“…In the Singapore population, the cutoff scores of 26/27 and 24/25 are used to detect aMCI and mild AD, respectively [8]. Moreover, a study on the Chinese version of the MoCA (C-MoCA) has shown that among the rural elderly people, the MoCA showed modest accuracy and was no better than the MMSE in detecting aMCI, especially in those with low education levels, due to the overwhelming effect of education relative to aMCI diagnosis on variations in C-MoCA performance [9]. Consistent with the above results, the C-MoCA was applied in our study and was successful in accurately screening the PD-MCI and PD-D patients.…”
Section: Discussionmentioning
confidence: 99%